The relationship between tourists' motivation and cultural and heritage attribute towards customer satisfaction - Sofinah Yussoff (2011)
Customer satisfaction is very important to ensure the provision of products and services provided to customers could achieve a satisfactory level. This is also important the context of Homestay Programme itself. Ancillary revenue generation by service provider or host family can be done by offering services that meet the needs and desires of visitors. Decreasing number of visitors come to the Homestay Programme in Wilayah Persekutuan Labuan in 2008. Therefore, this study is to identify the exact factors that can influence customer satisfaction, especially for local and foreign visitors who choose and participate in Homestay Programme in Labuan. There are two factors to measure customer satisfaction, which are tourists'motivation and the cultural and heritage. Quantitative and descriptive research approaches were applied in this study to describe the characteristics of related variables in this study. Through this study, there are several findings have been found. Among the eight hypotheses, explain the name of the dimensions that significant. Four of them were accepted. Therefore, underlying visitors' motivation,intellectuals has a significant relationship with customer satisfaction. Whereas for cultural and heritage, cultural attractions, experience of recreational and local services have a Significant relationship with customer satisfaction who visited Homestay Programme in Wilayah Persekutuan Labuan.